Phospholipid-grafted PLLA electrospun micro/nanofibers immobilized with small extracellular vesicles from rat adipose mesenchymal stem cells promote wound healing in diabetic rats. (26th September 2022) - Li, Jing; Yan, Shunshun; Han, Weiju; Dong, Zixuan; Li, Junliang; Wu, Qi; Fu, Xiaoling
Abstract: Small extracellular vesicles (sEVs) derived from mesenchymal stem cells (MSCs) can deliver a variety of bioactive factors to create a favorable local microenvironment, thereby holding huge potential in chronic wound repair. However, free sEVs administrated intravenously or locally are usually cleared rapidly, resulting in an insufficient duration of the efficacy. Thus, strategies that enable optimized retention and release profiles of sEVs at wound sites are desirable. Herein, we fabricated novel functional phosphoethanolamine phospholipid-grafted poly-l -lactic acid micro/nanofibers (DSPE-PLLA) to carry and retain sEVs from rat adipose MSCs, enabling the slow local release of sEVs. Our results showed that sEVs@DSPE-PLLA promoted the proliferation, migration and gene expression (Col I, Col III, TGF-β, α-SMA, HIF-1α) of fibroblasts. It also promoted keratinocyte proliferation. In addition, sEVs@DSPE-PLLA helped polarize macrophages toward the M2 phenotype by increasing the expression of anti-inflammatory genes (Arginase 1, CD 206, IL-10) and inhibiting the expression of pro-inflammatory genes (IL-1β, TNF-α). Further in vivo study in diabetic rat models showed that sEVs@DSPE-PLLA improved the wound-healing process by alleviating the inflammatory responses, stimulating cell proliferation, collagen deposition and angiogenesis. These results highlight the potential of using DSPE-grafted scaffolds for extracellular vesicle immobilization and suggest sEVs@DSPE-PLLA micro/nanofibers as promising functional wound dressings for diabetic wounds. Graphical Abstract: